2022
DOI: 10.20944/preprints202202.0341.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stable Laboratory Culture System for the Ctenophore <em>Mnemiopsis leidyi</em>

Abstract: Ctenophores are marine organisms attracting significant attention from evolutionary, molecular biology and ecological research. Here we describe an easy and affordable set-up to maintain a stable culture of the ctenophore Mnemiopsis leidyi. The challenging delicacy of the lobate ctenophores can be met by monitoring the water quality, providing the right nutrition, and adapting the handling and tank set-up to their fragile gelatinous body plan. Following this protocol allows stable laboratory lines, a continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…As a wider range of modern techniques has recently become available in ctenophores (e.g., single‐cell RNAseq [Sebé‐Pedrós et al, 2018] and connectomics [Burkhardt et al, 2023]) and ctenophore species have progressed towards becoming established lab models (e.g., culturing and CRISPR/Cas9 knock‐outs have been reported [Presnell et al, 2022; Soto‐Àngel et al, 2022]), new critical insights into the biology of their neurons have been revealed. Earlier studies have established such key approaches as electrophysiology and calcium imaging in ctenophores; however, it has been achieved only in comb plates (Moss & Tamm, 1987; Tamm & Terasaki, 1994) and muscles (Moroz et al, 2014; Ortiz et al, 2023), while direct measurements of neuronal activity have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a wider range of modern techniques has recently become available in ctenophores (e.g., single‐cell RNAseq [Sebé‐Pedrós et al, 2018] and connectomics [Burkhardt et al, 2023]) and ctenophore species have progressed towards becoming established lab models (e.g., culturing and CRISPR/Cas9 knock‐outs have been reported [Presnell et al, 2022; Soto‐Àngel et al, 2022]), new critical insights into the biology of their neurons have been revealed. Earlier studies have established such key approaches as electrophysiology and calcium imaging in ctenophores; however, it has been achieved only in comb plates (Moss & Tamm, 1987; Tamm & Terasaki, 1994) and muscles (Moroz et al, 2014; Ortiz et al, 2023), while direct measurements of neuronal activity have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high ecological plasticity of Mnemiopsis leidyi , it has become an important invasive species that colonized a wide range of marine environments and disrupted native ecosystems (Burton, 2008). Such a plasticity along with high regenerative capacity (Edgar et al, 2021) probably explains why M. leidyi has become a lab model organism (Martindale, 2022) that can adapt to the artificial conditions of aquarium facilities and be successfully cultured and reproduced over multiple generations (Presnell et al, 2022; Soto‐Àngel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of such non-conventional research models is nowadays essential to gain insight into the mechanisms underlying these complex biological traits at the cellular, molecular, and genetic level Arboleda et al, 2018;Ivankovic et al, 2019;Kassmer et al, 2019;Layden et al, 2016;Lechable et al, 2020;Mehta and Singh, 2019;Röttinger, 2021;Srivastava, 2022). Methods for the development and improvement of the entire life cycle in stable and reproducible laboratory conditions have recently been described for several marine vertebrates (Roux et al, 2020) and invertebrates (Carvalho et al, 2017;Gordon et al, 2020;Henry et al, 2020;Holland and Li, 2021;Lechable et al, 2020;Murabe et al, 2021;Soto-Àngel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%